Nationality and internationality of the socialist political economy with Chinese characteristics - Jinju Pang (China Political Economy (CPE), 2018)
Purpose As the crystallization of Chinese wisdom and the shared wealth of all humanity, the Socialist Political Economy with Chinese Characteristics (SPECC) not only reveals the specific traits of SPECC but also indicates the general rules of the global economic development, showing both nationality and internationality. The paper aims to discuss this issue. Design/methodology/approach Being aware of the nationality of the SPECC is of great importance. It requires to integrate the basic Marxist principles with the realities of China, and meanwhile draw lessons from, not just simply copy, the strengths of other countries. The authors must adhere to the basic principles of the SPECC. Findings From the perspective of past practices, the SPECC has not only provided theoretical guidance for China's reform and development, but has also given references to some countries, especially developing countries under reform and transition. Originality/value SPECC should be based on China's conditions and practices, absorb China's traditional cultural essences, draw lessons from other nations' positive theoretical and practical results, propose theoretical viewpoints independently and initially, and construct a distinct academic system and discourse system. In this way, China would work to develop the characteristics and advantages of the SPECC, and contribute Chinese wisdom to the development and improvement of world economics and economics theories.
Keywords: 330; Innovation and development; Internationality; Nationality; Socialist Political Economy with Chinese Characteristics (SPECC)